The five love languages of teenagers - Chapman, Gary D., 1938- (Northfield Pub, 2000)
Never has there been a more exciting -- or more challenging -- era in which to be (or parent) a teenager. The benefits of living in today's global society are great. But so are the dangers. Across the nation, pregnancies, sexually transmitted diseases, abortions, drug usage, homicide, and suicide have all become commonplace among teens. Yet despite these facts, moms and dads continue to have a dramatic impact on their children. Research shows that parents -- not peers -- exert the most significant influence in the life of a teen. And the door to that influence is love. The key to opening that door, according to Gary Chapman, Ph.D., is learning to express that love in a language that makes sense to your teenager. You can more effectively meet your adolescent's need for love -- and thus, better support your child in every area of life -- by gaining a better understanding of The Five Love Languages of Teenagers.